Aphid infestation in the phyllosphere affects primary metabolic profiles in the arbuscular mycorrhizal hyphosphere - Cabral, Carmina (2019)
While effects of (a)biotic stress events in the phyllosphere have been studied intensively, possible influences of stress on the arbuscular mycorrhizal hyphosphere has scarcely been investigated. We hypothesised that stress challenge in the phyllosphere could alter primary metabolite profiles of the hyphosphere - the mycelial network connecting plants. Donor plants, connected to receiver plants by mycelial networks, were aphid-challenged during 84 h. Primary metabolite profiles in the hyphosphere were investigated. Gene-expression of plant defence gene PR1 was measured in one of the receiver plants during the challenge. Hexose levels in the hyphosphere increased when donor plants were aphid-challenged. This change in metabolic profile was influenced by leaf sampling from receiver plant. PR1 expression increased in donor plants 48 h after challenge, and consequently 60 h after, in receiver plants. We conclude that aphid infestation of donor plants modified primary carbon metabolism in the hyphosphere. Plant defence response in receiver plants, occurred 12 h after detection of response in the aphid-challenged donor plants. While this work is the first to reveal primary metabolic profiles of the AM hyphosphere, more work is needed to elucidate the possible role of transient changes of hexose metabolism in stress response and signalling processes in the hyphosphere of connected plants.